Bamboo expansion promotes radial growth of surviving trees in a broadleaf forest - Gong, Chao; Zeng, Xiaoxia; Zhu, Xianglong; Huang, Wenhui; Compson, Zacchaeus G.; Ren, Zewen; Ran, Huan; Song, Qingni; Yang, Qingpei; Huang, Dongmei; Liu, Jun (Frontiers in Plant Science, 2023)
Considerable evidence indicates that some trees are more vulnerable than others during bamboo (Phyllostachys edulis) expansion, which can affect plant community structure and alter the environment, but there has been insufficient research on the growth status of surviving individuals in colonized forests. In this study, we compared the annual growth increment, growth rate, and onset, cessation, and duration of radial growth of Alniphyllum fortunei, Machilus pauhoi, and Castanopsis eyrei in a bamboo-expended broadleaf forest (BEBF) and a bamboo-absent broadleaf forest (BABF) using high-resolution point dendrometers. We found that the annual radial growth of A. fortunei, M. pauhoi, and C. eyrei was 22.5%, 172.2%, and 59.3% greater in BEBF than in BABF, respectively. The growth rates of M. pauhoi and C. eyrei in BEBF were significantly higher than in BABF by13.9 μm/d and 19.6 μm/d, whereas A. fortunei decreased significantly by 7.9 μm/d from BABF to BEBF. The onset and cessation of broad-leaf tree growth was later, and the growth duration was longer in BEBF compared to BABF. For example, A. fortunei and M. pauhoi in BEBF had more than one month longer growth duration than in BABF. Additionally, the nighttime growth rates of some surviving broad-leaf trees in BEBF was significantly higher than that in BABF. These results suggest that the surviving trees have plasticity and can adapt to atmospheric changes and competitive relationships after expansion of bamboo in one of two ways: by increasing their growth rates or by modifying onset and cessation of growth to extend the growth duration of trees or avoid the period of intense competition with bamboo, thereby growing better. Our research reveals for the first time how the growth of surviving broad-leaf trees adjusts to bamboo expansion. These results provide insights into how biological expansions impact primary production and have implications for forest management in the Anthropocene.